Der lyrische Augenblick: Eine Denkfigur der Romania - Herold, Milan; Bernsen, Michael (Mimesis, 2015)
Every moment represents eternity - Goethe's words poignantly capture the nuances and special complexity of the term "moment." It can refer to such varied notions as ecstasy, empty presence, and epiphany. This volume examines the semantic richness of the "moment" using paradigmatic examples from Italian, French, Spanish, Portuguese, and Brazilian poetry from their beginnings to the modern era
Description based upon print version of record
Keywords: Electronic books; Aufsatzsammlung; Geschichte; Augenblick; Lyrik; Romanische Sprachen